Functional electrical stimulation reduces pain and shoulder subluxation in chronic post-stroke patients? - Silva, Willian Vasconcellos da; Cirne, Gabriele Natane de Medeiros; Filho, Edson Meneses da Silva; Cacho, Enio Walker Azevedo; Lopes, Johnnatas Mikael; Cacho, Roberta de Oliveira; Baroni, Marina Pegoraro (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Shoulder subluxation is a common complication of cerebral vascular accident (stroke) and the use of Functional Electrical Stimulation (FES) within the rehabilitation process is extremely important. Objective: To analyze the therapeutic effects of FES in the treatment of chronic shoulder subluxation in post-stroke patients. Method: This is a case study of patients with radiologically subluxation confirmed, who were randomly divided into two groups: Control Group (CG) and Treatment Group (TG). Patients were assessed before and after treatment and at the 2-month follow-up. The assessment consisted of the modified Ashworth scale; passive goniometry; Fugl-Meyer scale; McGill pain questionnaire and evaluation of shoulder subluxation by radiography. The CG did not receive physiotherapeutic intervention; and TG underwent 20 sessions of motor kinesiotherapy and FES associated with functional exercises with a total duration of 1 hour, three times a week, for 7 weeks. The data were analyzed descriptively. Results: The mean age of CG participants was 82.5 ± 1.5 years and of the TG was 70.5 ± 13.5 years. All of them were retired, sedentary, non-smokers/alcoholics and had hemiparesis on the left side. There was an approximate increase of 10o for most joint movements of the shoulder, improvement in McGill scale scores and reduction of shoulder subluxation in TG patients. Conclusion: FES associated with functional movements was effective in reducing the degree of subluxation of the shoulder joint and decreased pain in subjectsin the chronic phase of the post-stroke.